Sintakmatik dalam Analisis Struktur Kalimat Bahasa Indonesia: Syntax in Indonesian Sentence Structure Analysis - Nainggolan, Kristiani (Information Technology and Science(ITScience), 2025)
This study examines syntagmatic relations in Indonesian sentence structures and their implications in language learning. The background of this study is based on the importance of understanding syntagmatic relations as the basis for constructing meaningful and grammatical sentences in Indonesian language learning. Using a descriptive-qualitative approach based on literature studies, this study analyzes syntagmatic relations at three linguistic levels: phonology, morphology, and syntax. The study results indicate that syntagmatic relations are linear relations between language elements whose presence sequentially forms a meaningful structure. At the phonological level, this relationship appears in the sequence of phonemes that cannot be changed without changing the word's meaning. In morphology, syntagmatic relations are seen in the arrangement of morphemes by grammatical rules.Meanwhile, at the syntactic level, this relationship plays a vital role in forming grammatical and coherent sentences. This study also shows that understanding syntagmatics is very important in teaching Indonesian, especially in improving students' abilities in constructing and analyzing sentence structures systematically. The synthesis of Ferdinand de Saussure's structural theory with a modern linguistic and pedagogical approach shows the real contribution of the syntagmatic concept in the context of language education. This study concludes that syntagmatic relations are essential in analyzing language structure and, practically, in increasing the effectiveness of Indonesian language learning.